2022
DOI: 10.1155/2022/1135452
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis on a Malaria Model with Relapse Preventive Treatment and Saturated Fumigation

Abstract: Malaria has produced health issues in many parts of the world. One of the reason is due to the recurrence phenomenon, which can happen years after the main infection has appeared in the human body. Furthermore, the fumigation intervention, which has become a major worry in several regions of the world, has yielded unsatisfactory results, as seen by the high number of cases reported each year in several African countries. We present a novel mathematical model that integrates tafenoquine treatments to prevent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As mentioned before, one of the leading mitigation measures over time has been the use of ITNs, which has had a significant impact in the reduction of malaria cases, in combination with other mitigation strategies [ 1 , 7 , 12 , 14 , 41 ]. This result has been supported and analyzed by mathematical models [ 35 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 58%
“…As mentioned before, one of the leading mitigation measures over time has been the use of ITNs, which has had a significant impact in the reduction of malaria cases, in combination with other mitigation strategies [ 1 , 7 , 12 , 14 , 41 ]. This result has been supported and analyzed by mathematical models [ 35 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 58%
“…As mentioned by [31], vector bias phenomena cannot be ignored in the malaria transmission process since it gives a higher preference to mosquitoes to bite infected humans. Unlike the proposed vector bias model by the author in [15,29,30,53], here, we consider optimal control and asymptomatic cases in our analysis. With this model, infected humans are divided into two compartments, namely, asymptomatic and symptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models have been employed by many researchers to comprehend how diseases may spread among populations, as demonstrated in references [15][16][17][18]. In the context of malaria transmission models, numerous approaches have been explored to assess how malaria spreads, considering factors such as vector bias [19,20], repellent [21,22], and treatment [23].…”
Section: Introductionmentioning
confidence: 99%
“…Common symptoms of malaria include headache, profuse sweating, nausea, severe anaemia, high or moderate fever, severe or moderate shaking chills, morbidity, infant mortality, abdominal pain, muscle pain, etc. [5]. Recent studies have shown there is in-1 Duru et al / J. Nig.…”
Section: Introductionmentioning
confidence: 99%